Sguardi narrativi e prospettive sulla disabilità nella letteratura per l’infanzia oggi - Pacelli, Silvia (Studi sulla Formazione/Open Journal of Education, 2024)
Contemporary children’s literature is paying an increasing attention to the discovery of characters with disabilities and works for young people are widely used as a cultural mediation tool to promote attitudes of inclusion. Literary representations of disability are not neutral and raise some critical questions. The contribution aims to reflect on the authenticity of such representations, the interpretative mediations to which they are subjected and the desire of people with disabilities to self-represent themselves.